Konten Dakwah Penceramah Perempuan: Analisis Respon Audien pada 'Suara Muslimah' di Kanal NU Online - Lukman Hakim; Agus Riyadi; Ali Murtadho (Jurnal Komunikasi Islam, 2023)
This article aims to examine the audience's response to the da'wah content broadcasted by "Suara Muslimah" on the NU online YouTube channel. The research method used in this study was a qualitative text analysis. Through the examination of 162 netizen comments on four episodes of "Suara Muslimah" programs, the findings have shown that the majority of audiences have positive responses to da'wah content aired by the "Suara Muslimah" program, although some audiences have responded negatively and others made irrelevant comments to the content. Additionally, the audience also provided responses related to cognitive, affective, and conative aspects.